Growth, Inequality, and Poverty : Looking Beyond Averages - Ravallion, Martin (World Bank, Washington, DC, 2014)
The evidence is compelling that the poor in developing countries do typically share in the gains from rising aggregate affluence and in the losses from aggregate contraction. But how much do poor people share in growth? Do they gain more in some settings than others? Do some gain while others lose? Does pro-poor growth mean more or less aggregate growth? Recent theories and evidence suggest some answers, but deeper microeconomic empirical work is needed on growth and distributed change. Only then will we have a firm basis for identifying the specific policies and programs needed to complement and possibly modify growth-oriented policies.